Analisis Kesalahan Penulisan Kalimat Sederhana Bahasa Arab Siswa Kelas X di MAN 1 Kota Makassar - Syahruni Syahruni; Fatkhul Ulum; Mardhiana Jamal (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2026)
This study aimed to obtain data and information regarding the types of errors and to identify the causal factors of errors in writing simple Arabic sentences among tenth grade students at MAN 1 Makassar City. This research employed a quantitative descriptive method with a sample of 25 students. Data were collected through a writing test instrument and a questionnaire. The findings revealed that the students' writing ability was categorized as low, with an average score of 29.2. A total of 463 errors were identified, comprising: harakat (vowel diacritic) errors (292 errors or 63.07%), errors in connecting the mubtada' (72 errors or 15.55%), errors in completing the khabar (44 errors or 9.50%), and errors in constructing nominal sentences—jumlah ismiyyah (55 errors or 11.88%). The test results were inconsistent with the questionnaire results, as the questionnaire indicated that students tended to have positive perceptions toward learning Arabic writing. The errors were attributed to two factors: internal factors including low mastery of nahwu-sharaf grammatical rules and limited vocabulary; and external factors including insufficient writing practice, less varied teaching methods, and an unsupportive learning environment.